Analysis of Budget Realization to Assess the Effectiveness and Efficiency of the Social Rehabilitation Sector of Children and the Elderly: (Bogor Regency Social Service) - Karinna Tri Maharani Karinna; MN Rizqi; M Anwar Masruri (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2025)
This study aims to analyze budget realization to evaluate the effectiveness and efficiency of financial management in the Social Rehabilitation Sector for Children and the Elderly at the Bogor Regency Social Services Office during the 2022–2024 period. Using qualitative descriptive methods, this study found that these programs consistently achieved high effectiveness, with 100% achievement of physical targets each year. Budget utilization was also classified as